Cuentas por cobrar del comercial franklin de la ciudad de Babahoyo durante el 2021 – 2022. - España Valle, Andy Iván (2023)
The present case study with the theme "Accounts receivable from the Franklin commercial located in the city of Babahoyo in the period 2021 - 2022", aims to analyze the accounts receivable and their impact on liquidity through the financial information of the company in order to determine the weight of accounts receivable from the commercial through horizontal analysis, identify the liquidity index that it has and emphasize the importance of carrying out a correct management of this item, and the recovery of the portfolio so that customer indebtedness does not continue to grow. In the development of the research, the theoretical bases related to accounts receivable, credit, credit sales, financial indicators and horizontal analysis were examined; this information was essential for the preparation of the results. Qualitative and quantitative approaches were used, in addition, the inductive-deductive method and the interview were used as a research tool, which allowed us to see how the commercial is affected by the increase in the portfolio and the absence of credit policies. From the results of the case study it was possible to demonstrate that the company does not have effective control over the credit portfolio, because compliance with customer payments is not verified, which leads to an increase in the delinquency level.